REDUCING POLUTTANT EMMISSION OF BALI CATTLE FED AGRICULTURAL WASTE DIETS THROUGH GIVEN BIOSUPPLEMENT OF SUPERIOR LIGNOCELLULOLYTIC BACTERIA OF RUMEN AND TERMITES - A. A. P. P., Wibawa; Cakra, I G. L. O.; Mudita, I M.; Partama, I. B. G. (Jurnal Peternakan Tropika, 2017)
A Research had been carried out to reduce the pollutant emission of Bali cattle fed  basal diet based on agricultural waste (fermented rice straw) through given selective rumen and termites lignocellulolytic bacteria biosupplement. Twelve Bali cattle were used in this experiment. Three selective inocullant (BR 23 T 14 ; BR 24 T 13 ; BR 34 T 12 ) which result first research 2015 were used in this research for production biosupplement. This experimen used a Randomized Block Designed with four treatments and three blocks. The first treatment was basal diet based on agricultural waste with biosupplement without selective inocullant (A), while the other three treatments were fed biosupplement produced with first superior inocullant/BR 23 T 14 (B), fed biosupplement produced with second superior inocullant/BR 24 T 13 (C), and fed biosupplement third superior inocullant/BR 34 T 12 (D). The result showed that fed biosupplement superior lignocellulolytic bacteria inoculant has reduce (P<0,05) rumen methane emmission based on totally VFA, concentration and production of fecal amonia, concentration and production  urine amonia. Fed first superior biosupplement (treatment B) has lowest pollutant emmission on bali cattle fed agricultural waste basal diet Key word: Bali Cattle, Fermentation, Local Waste, Rumen Liquor